Optimasi Metode Ekstraksi Daun Sirih Hitam (Piper Sp.) Terhadap Kandungan Metabolit Sekunder: Optimization of Extraction Method of Black Betel Leaf (Piper Sp.) Against Secondary Metabolite Content - Jamal Habibullah; Risna Agustina; Fajar Prasetya (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
The black betel plant (Piper Sp.) Has been empirically used by the public for a treatment. This plant has the potential to be developed into pharmaceutical products made from natural ingredients, so an extraction method is needed that can be used as a standard in the development of this plant. The research aims to determine the effect of stirring speed, solid-liquid ratio and sample surface area in the extraction method and to determine the profile of the extraction method. the optimum black betel leaf based on the yield parameters of the extract and the TLC profile. This research is an experimental study conducted by extracting black betel leaves using the maceration method which is influenced by several conditions, namely, with a stirring speed of 300 rpm; 400 rpm; 500 rpm, 1: 5 solid to liquid ratio; 1:10; 1:15 and the surface area of the chopping sample using a blender; 1x1 cm; 2x2 cm. Then the extract yield was calculated and the TLC profile observations were made. The results showed that the stirring speed, the solid-liquid ratio and the surface area of the sample affected the yield of the extract. However, the stirring speed and surface area of the sample did not affect the stain pattern on the TLC profile, while the liquid solid ratio affected the stain pattern on the TLC profile, and the optimum extraction method for the extract yield on black betel leaf was stirring speed of 300 rpm, solid to liquid ratio. ratio of 1:15 and the surface area of the chopped sample using a blender.